Auditoría financiera para determinar la razonabilidad de los estados financieros de almacenes totalhome de la ciudad de Riobamba período 2017 - Luis Fernando, López Yumancela (2020)
The name of this research work called “FINANCIAL AUDIT TO DETERMINE THE REASONABLENESS OF THE FINANCIAL STATEMENTS OF TOTALHOME STORES IN RIOBAMBA CITY DURING 2017”. The aim of this research was to determine the efficiency level of the company. The main objective is to develop a financial audit about TOTALHOME Company in Riobamba during 2017. In the research methodology the deductive and analytical methods were employed. They were critical to the development of the audit. The type of design. Finally, Financial Audit phases involved a planning visit in order to obtain useful information about the development of the audit; in the implementation, researchers analyzed and select components. All of them unable to determine the respective findings related to communicational results. Therefore, it was possible to obtain a final audit report which gave an opinion on the reasonableness of the Financial Statements of the company TOTALHOME.